4 - Post-Independence Development Planning in Ghana and Tanzania: Agriculture, Women and Nation-building - Britwum, Akua O. (Africa Development, 2022)
This article analyses development planning in post-independence Ghana and Tanzania, particularly related to agriculture, in contrast with the contemporary neoliberal subsumption of African economies to market forces. The article derives lessons from both their successes and shortcomings. Ghana and Tanzania’s experiences suggest the importance of agricultural transformation for national self-sufficiency; development planning as a mechanism to link all sectors of the economy; and the key strategic potential of the state in production, distribution and employment creation. Key shortcomings included the inability to fully de-link national economies from the global capitalist political economy, break dependence on earnings from cash crop exports, and the political and economic marginalisation of women in post-independence development planning. The article suggests that progressive development planning that centres the pursuit of gender justice is a critical starting point for imagining and pursuing alternatives to neoliberalism.